2004
DOI: 10.1055/s-2004-820878
|View full text |Cite
|
Sign up to set email alerts
|

Water Shortage Affects the Water and Nitrogen Balance in Central European Beech Forests

Abstract: Whilst forest policy promotes cultivation and regeneration of beech dominated forest ecosystems, beech itself is a highly drought sensitive tree species likely to suffer from the climatic conditions prognosticated for the current century. Taking advantage of model ecosystems with cool-moist and warm-dry local climate, the latter assumed to be representative for future climatic conditions, the effects of climate and silvicultural treatment (different thinning regimes) on water status, nitrogen balance and growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 71 publications
3
71
1
1
Order By: Relevance
“…Conversely, the quick response of leaf stomatal conductance (g s ) confirms that control of the transpiration is a very sensitive and short-term response of plants to reduced water supply (cf. Gessler et al, 2004). The finding that g s was mainly reduced in July and only marginally significantly in September clearly reflects the fact that our rain reduction was not absolute but proportional.…”
Section: Roof Effects On Evapotranspiration Leaf Stomatal Conductancmentioning
confidence: 58%
“…Conversely, the quick response of leaf stomatal conductance (g s ) confirms that control of the transpiration is a very sensitive and short-term response of plants to reduced water supply (cf. Gessler et al, 2004). The finding that g s was mainly reduced in July and only marginally significantly in September clearly reflects the fact that our rain reduction was not absolute but proportional.…”
Section: Roof Effects On Evapotranspiration Leaf Stomatal Conductancmentioning
confidence: 58%
“…In gaps, moisture and nutrient status may be particularly favourable for drought sensitive European beech seedlings when young individuals compete with surrounding ground vegetation (Bolte et al 2007). Gessler et al 2004 showed that not only water shortage has a negative effect on European beech water budget but it also constrains its nitrogen supply. Light conditions may also positively influence the growth response of beech seedlings to soil fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Other processes related to the short and long term acclimation of trees to drought need be better understood. Finally, nitrogen nutrition and cycling is likely to be modified by drought [48], and the impact of nutrient shortage under water deficit has to be quantified under various levels of site fertility and among drought tolerant, resistant or avoiding tree species.…”
Section: Conclusion: New Challenges For Scientistsmentioning
confidence: 99%